Juridical review and implementation of child custody rights in court decision number: 144/PDT.G/2021/PN.SIM - Ginting Munthe, Hottua Natalia; Sidauruk, Jinner (Institute Of computer Science (IOCS), 2025)
A family is formed by a legal marriage event both according to religion and the State and in accordance with applicable laws and regulations. In a marriage, it is certain to crave the presence of children to fill a family and produce a complete household. In addition, children are also the successors of their parents' descendants and as the successors of the nation. After having children, parents have the main and important obligations and responsibilities in assisting the growth and development of children. The role of parents is the first teaching in a child's life in the process of shaping and building a good child's character is the obligation of parents in caring for, maintaining and educating until their children grow up. This parental obligation is certainly supported and regulated in Article 45 of Law Number 1 of 1974 concerning Marriage. However, there are many problems in the household that cause conflict between husband and wife in a marriage which causes various problems. One of the problems that occurs as a result of divorce is the transfer of child custody. This research is a type of research normative juridical research on the provisions of Marriage Law number 1 of 1974, with data analysis using a statutory approach and secondary data using scientific journals.